2022
DOI: 10.3389/fphar.2022.937531
|View full text |Cite
|
Sign up to set email alerts
|

Novel GIRlncRNA Signature for Predicting the Clinical Outcome and Therapeutic Response in NSCLC

Abstract: Background: Non–small cell lung cancer (NSCLC) is highly malignant with driver somatic mutations and genomic instability. Long non-coding RNAs (lncRNAs) play a vital role in regulating these two aspects. However, the identification of somatic mutation-derived, genomic instability-related lncRNAs (GIRlncRNAs) and their clinical significance in NSCLC remains largely unexplored.Methods: Clinical information, gene mutation, and lncRNA expression data were extracted from TCGA database. GIRlncRNAs were screened by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…However, no study to date had demonstrated the relationship between APTR and lung cancer. It showed that AC008278.2 was a protective lncRNA was one of 19 genomic instability-related lncRNAs that correlated with somatic mutation pattern, immune microenvironment infiltration, immunotherapeutic response, drug sensitivity, and survival of NSCLC patients (Zhang et al, 2022). While as for PAN3-AS1 and AC093911.1, little has been studied in current diseases or molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study to date had demonstrated the relationship between APTR and lung cancer. It showed that AC008278.2 was a protective lncRNA was one of 19 genomic instability-related lncRNAs that correlated with somatic mutation pattern, immune microenvironment infiltration, immunotherapeutic response, drug sensitivity, and survival of NSCLC patients (Zhang et al, 2022). While as for PAN3-AS1 and AC093911.1, little has been studied in current diseases or molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluated the prognostic risk of NSCLC patients using the expression level of 19 lncRNAs: LINC01067* (-0.1595) + AC012645. [33]. Another investigation predicted survival of patients with ADC directly using the methylation level of three sites:…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of RAB42 for cancer patients was assessed by 4 clinical outcomes: overall survival (OS), disease-specific survival (DSS), progression-free survival (PFS) and disease-free survival (DFS). Prognostic indicators, including hazard ratios (HRs), 95% confidence intervals (95% CIs) and p values, were calculated under standard conditions ( Zhang et al, 2022 ; Su et al, 2024 ). A result was considered significant when p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…R packages “pROC” and “ggplot2” were used to determine the receiver operating characteristic (ROC)-area under the curve (AUC) values of RAB42. In principle, AUC values greater than 0.8 are considered to be high reliability ( Zhang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%